IMPLEMENTATION OF THE AL-QUR'AN MEMORIZATION LEARNING METHOD AS A SPECIAL PROGRAM TO IMPROVE STUDENTS' RELIGIOUS CHARACTER AT UNISMUH MAKASSAR JUNIOR HIGH SCHOOL - Mashud, Amri; Muchtar, Ilham; Dewanti, Rahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research aims to determine the implementation of the Al-Qur'an tahfidz learning method as a special program in improving students' religious character at Unismuh Makassar Middle School and to find out the indicators of success in implementing the Al-Qur'an tahfidz learning method as a special program for improving students' religious character at Makassar Unismuh Middle School and the supporting and inhibiting factors for implementing the Al-Qur'an tahfidz learning method as a special program for improving students' religious character at Makassar Unismuh Middle School. The research method used is a qualitative approach with a case study research type. Data collection is carried out through observation, interviews and documentation to ensure the accuracy and validity of the information obtained. From the results of the study of the implementation of the Al-Qur'an memorization learning method as a special program in improving the religious character of students at SMP Unismuh Makassar, it can be concluded that the special program for Al-Qur'an memorization, several methods are often used including the deposit method, talaqqi method, sima'an method and Sabaq, Sabqi, Manzil (SSM) method. The evaluation measures the indicator of the success of Al-Qur'an learning, there are 3 types of evaluations in this school including daily evaluation, monthly evaluation and semester evaluation. While the supporting and inhibiting factors for Al-Qur'an learning are several things, namely supporting factors include motivation from teachers and parents, adequate facilities and infrastructure while inhibiting factors include laziness, boredom, boredom caused by the child himself.